Privacy-preserving digital ecosystems: The role of blockchain technology in healthcare, finance, and smart cities - Divyang Joshi; Paresh Patel; Hiren Harsora; Amita Garg; Himal Goswami; Shailak Jani (International Journal of Business and Management (IJBM), 2026)
The accelerating digitisation of healthcare, financial services, and urban governance has intensified concerns regarding data privacy, security, and unauthorised data exploitation. Traditional centralised data management architectures exhibit inherent vulnerabilities, including single points of failure, susceptibility to cyberattacks, and limited individual control over personal information. This study examines blockchain technology as a transformative solution for privacy preservation across these three critical sectors. The analysis explores foundational cryptographic mechanisms including zero-knowledge proofs, homomorphic encryption, secure multi-party computation, and decentralised identity systems that enable verifiable data transactions without exposing sensitive information. Through real-world case studies, including Estonia's national e-Health system, MIT's MedRec, JPMorgan's Quorum platform, India's central bank digital currency pilots, and Dubai's Blockchain Strategy, the study demonstrates blockchain's capacity to enhance patient data autonomy, ensure financial transaction integrity, and secure citizen-centric smart city services. The discussion critically addresses persistent challenges, including scalability constraints, regulatory compliance complexities, energy consumption concerns, and ethical tensions between transparency and privacy. Looking forward, the study identifies promising trajectories, including integration with artificial intelligence, quantum-resistant cryptography, and edge computing architectures. This study concludes that blockchain technology, despite its limitations, represents a foundational infrastructure for building resilient, privacy-preserving digital societies, and calls for sustained interdisciplinary research and proactive policy frameworks to facilitate its responsible adoption.